Post-growth and the lack of diversity in the scenario framework - Rawad El Skaf (Post-growth Economics Network (PEN), 2025)
Scenarios and pathways, as defined and used in the "SSP-RCP scenario framework", are key in last decade's climate change research and in the latest report of the Intergovernmental Panel on Climate Change (IPCC). In this framework, Shared Socioeconomic Pathways (SSP) consist of a limited set of alternative socioeconomic futures, that are both represented in short qualitative narratives and with quantitative projections of key drivers. One important use of the computationally derived SSPscenarios is to do mitigation analysis and present a "manageable" set of options to decision-makers. However, all SSPs and derivatively SSP-scenarios in this framework assume a globally growing economy into 2100. This, in practice, amounts to a value-laden restriction of the space of solutions to be presented to decision-makers, falling short of IPCC's general mandate of being "policyrelevant and yet policy-neutral, never policy-prescriptive". Yet, the Global Economic Growth Assumption (GEGA) could be challenged and in practice is challenged by post-growth scholars. However, for post-growth mitigation scenarios to be constructed, explored, and assessed more systematically, they need to be fully integrated into the scenario framework. This is not done yet. I argue, from a philosophy of value-laden science perspective, that this should be done and propose two ways. This integration follows from and satisfies a diversity criterion, which derivatively enhances the framework's "objectivity" and the IPCC's policy-neutrality.
Keywords: 330; Klimawandel; Szenariotechnik; Prognoseverfahren; Wirtschaftswachstum